Distribución, reproducción y alimentación de Syacium gunteri Ginsburg (Pisees: Bolhidae), en el Golfo de México* - García-Abad, Ma de la C. (Universidad de Costa Rica, 1992)
The flat fish, Syacium gunteri is a dominant species of the demenal communities in the Southem Gulf of Mexico. This flounder is marine, non-estuarine-dependent and is distributed in all of the Campeche Sound area, principally towards the westem region. It occun mostly in terrigenous sedirnent (mud and fme sands) with low CaC03 and high organic contents. Females mature at a total length of 60 mm; 96 mm is the size of fint maturity. Reproduction occun froom May to September: there is only ene reproduction period per year. It is a third order consurner which mainly feeds on cmstaceans (peneid shrimps) and fish to a lesscr degree. h has diurnal food habits and rests at night buried in sand.